Quantitative resistance to clubroot infection mediated by transgenerational epigenetic variation in Arabidopsis. Issue 1 (30th November 2018) - Liégard, Benjamin; Baillet, Victoire; Etcheverry, Mathilde; Joseph, Evens; Lariagon, Christine; Lemoine, Jocelyne; Evrard, Aurélie; Colot, Vincent; Gravot, Antoine; Manzanares‐Dauleux, Maria J.; Jubault, Mélanie
Summary: Quantitative disease resistance, often influenced by environmental factors, is thought to be the result of DNA sequence variants segregating at multiple loci. However, heritable differences in DNA methylation, so‐called transgenerational epigenetic variants, also could contribute to quantitative traits. Here, we tested this possibility using the well‐characterized quantitative resistance of Arabidopsis to clubroot, a Brassica major disease caused by Plasmodiophora brassicae . For that, we used the epigenetic recombinant inbred lines (epiRIL) derived from the cross ddm1‐2 × Col‐0, which show extensive epigenetic variation but limited DNA sequence variation. Quantitative loci under epigenetic control (QTL epi ) mapping was carried out on 123 epiRIL infected with P. brassicae and using various disease‐related traits. EpiRIL displayed a wide range of continuous phenotypic responses. Twenty QTL epi were detected across the five chromosomes, with a bona fide epigenetic origin for 16 of them. The effect of five QTL epi was dependent on temperature conditions. Six QTL epi co‐localized with previously identified clubroot resistance genes and QTL in Arabidopsis. Co‐localization of clubroot resistance QTL epi with previously detected DNA‐based QTL reveals a complex model in which a combination of allelic and epiallelic variations interacts with the environment to lead to variation in clubroot quantitative resistance.